The Americas in the Spanish world order : the justification for conquest in the seventeenth century - Muldoon, James, 1935- (University of Pennsylvania Press, 1994)
Juan de Solorzano Pereira (1575-1654) was a lawyer who spent eighteen years as a judge in Peru before returning to Spain to serve on the Councils of Castile and of the Indies. Considered one of the finest lawyers in Spain, his work, De Indiarum Jure, was the most sophisticated defense of the Spanish conquest of the Americas ever written, and he was widely cited in Europe and the Americas until the early nineteenth century. In this work he not only drew on traditional legal and the logical materials used to defend the conquest, but also employed anthropology and history to compare the social and political development of the New World with that of the Old. His work, with that of the Spanish School of international law theorists generally, is often seen as leading to Hugo Grotius and modern international law. However, as James Muldoon shows, the De Indiarum Jure represents the fullest development of a medieval Catholic theory of international order that provided an alternative to the Grotian theory. The Americas in the Spanish World Order offers a sophisticated evaluation of the significance of the legal and theological debates that attended the Spanish conquest of the New World. It will be of interest to students and scholars of medieval and early modern Spanish and legal history.